THE INFLUENCE OF KNOWLEDGE MANAGEMENT AND TALENT MANAGEMENT ON ORGANIZATIONAL EFFECTIVENESS IN RADIO STATIONS MANADO - Wowiling, Pamela G.; Lapian, Joyce S.L.H.V.; Tielung, Maria V. J. (FEB Universitas Sam Ratulangi Manado, 2021)
Along with the current technology development and the newest development all around the world, as one of the oldest media ever, Radio Stations in the world, especially Manado, are expected to continue to maintain their existence in this digital era. To be able to continue their presence and keep exist in this era, radio stations must be focused on the goal of finding and retaining people who have the necessary knowledge and place them in the right position in the organization. The purpose of this research is to find out the influence of Knowledge Management and Talent Management on Organizational Effectiveness partially or simultaneously. The data in this study consisted of primary data that is questionnaires that were distributed to several radio stations in Manado. This research uses Quantitative Method and analyzes the research data using Multiple Linear Regression analysis. The research sample was 39 employees who worked in several Radio Stations in Manado. The results of this study prove that Knowledge Management and Talent Management significantly influence partially and simultaneously on the Organizational Effectiveness of several Radio Stations in Manado.Â Keyword: Knowledge Management, Talent Management, Organizational Effectiveness